Plan de negocios para la creación de un restaurante de comida rápida en el sector turístico de Minca, corregimiento del Distrito de Santa marta, Departamento del Magdalena (2022)
This document outlines a research model associated with the creation of a business scheme in the restaurant sector, supporting the creation of companies and developing a type of mixed research, where primary and secondary methods of recognition are used to achieve an optimal project formulation process. Tools that were acquired throughout the professional career were implemented, developing a project that has as its objective a marketing plan with a promotion, product, price and place strategy, which allowed the restaurant to be known as an efficient and sustainable business. that can provide society with the availability of a scarce product in the area. Points such as; The planning for the marketing plan for brand recognition, internal and external factors that may represent an advantage or disadvantage towards the market that it intends to target. This business plan proposal was taken as an opportunity to publicize some of the shortcomings that occur in the tourist sector of Minca, since currently there is not a wide variety of establishments that offer similar products such as restaurants of fast foods, for which culinary trends were implemented that encompass a wide variety of tastes and preferences, creating brand value for the customer. Preliminary information was taken into account near the area where the fast food restaurant was intended to be established, the advantages and disadvantages that it could bring were taken into account, in the same way the characteristics of the population to be studied, the variables under study , the estimation of the size and sample; Providing solutions to the exposed problems, weaknesses or aspects to be improved within this project, obtaining significant results that not only will help to carry out this degree proposal, but also brought with it an innovative, fresh, new restaurant open to the public that with multicultural tastes, open to trying different dishes but at the same time with a touch of home.